PENGGUNAAN METODE FUZZY INFERENCE SYSTEM (FIS) MAMDANI DALAM PEMILIHAN PEMINATAN MAHASISWA UNTUK TUGAS AKHIR - Yulmaini - (Jurnal Informatika, 2015)
Fuzzy logic is a branch of artificial intelligence to build expert systems. Fuzzy logic is often used as problem solver in a system that does not use numbers, but linguistics or unobvious variables. One of the implementation of fuzzy logic is decision making in determine the topic of final assignment, especially bachelor thesis. IBI Darmajaya has some study programs in the faculty of Computer Science. One of those study programs is Informatics Engineering. The study program of Informatics Engineering leads the students to the specialization of Web Development and Multimedia, Software Engineering, or Expert System for their bachelor thesis. During this time, the specialization that taken by students is not actually what they expert in or the grade they earn from each subject. Usually, students take the specialization because of many students take that field. As the result, they have difficulties to finish their bachelor thesis. This research uses Fuzzy Inference System of Mamdani with 12 input variables, 37 rules, and 3 thesis specializations. This research aims to generate a fuzzy system as a decision maker to determine the thesis specialization. Key words: Thesis Specialization, FIS-Mamdani